PENGARUH PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN DAN INFORMASI ASIMETRI TERHADAP TIMBULNYA KESENJANGAN ANGGARAN - Savitri, Enni; Sawitri, Erianti (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This study aims to find empirical evidence to support the notion that there aresignificant between budget participation, budget emphasis and informationasymmetry on the incidence of budgetary slack in Kampar District Government oneducation. In this study, the samples taken were 140 people from 35 regional workunits (on education) which consists of the Chief on education, public and officialdomsub-section, sub-section program planning, and finance sub-sections, which areinvolved in the preparation of the budget on education district government Kampar.Data collected through direct observation and surveys obtained by means of thedistribution of questionnaires to the respondents. This study used multiple linearregression analysis model (multiple linear regression). The results showed thatbudget participation, budget emphasis and information asymmetry affect thebudgetary slack.Budgetary participation variables significantly affect the incidence ofbudgetary slack. Thus, participation budget the greater cause budgetary slack is thegreater. The target budget is used as a measure of performance of subordinates,and / or the presence of monetary incentives such as bonuses, raises budgetemphasis. Information asymetry increases in the budgeting process, it will triggerincreased budgetary slack anyway.Keyword:Budgetary participation, budget emphasis, information asymmetry, andbudgetary slack